Relationship of left ventricular diastolic dysfunction with quality of life in heart failure patients with reduced ejection fraction (HFrEF) - Khaidirman, Sophia K.; Hasan, Harris; Andra, Cut A.; Lubis, Hilfan AP.; Dangana, Amos; Haykal, T. Bob (Narra J, 2024)
Heart failure is a complex clinical manifestation due to diastolic dysfunction and systolic dysfunction of the left ventricle (LV). Diastolic dysfunction of the LV plays an important role in worsening the quality of life (QoL) in heart failure patients. The aim of this study was to assess the relationship between the severity or grade of LV diastolic dysfunction and QoL in heart failure with reduced ejection fraction (HFrEF) patients. A retrospective cohort study was conducted at the Cardiac Center of H. Adam Malik Hospital, Medan, Indonesia, from January 2022 to December 2022. This study included inpatients and outpatients aged above 18 years who were diagnosed with HFrEF, identified by echocardiography with an ejection fraction of ≤40%. Echocardiography was performed to evaluate left ventricular diastolic dysfunction, and QoL was assessed using the Minnesota Living with Heart Failure Questionnaire (MLHFQ) 6–12 months after the severity of LV diastolic dysfunction was confirmed. The MLHFQ was classified into good and poor QoL. The severity of LV diastolic function was measured using the E/A ratio, mean E/e' ratio, tricuspid regurgitation velocity (TR Vmax), and left atrial volume index (LAVI), and was classified into grades I, II, and III. The relationships between the severity of diastolic dysfunction and other factors with QoL were measured using Chi-squared, Fisher's exact test, or Mann-Whitney test, as appropriate. A total of 96 patients were included in the study, of which 56 (58.3%) patients had grade I, 12 (12.5%) had grade II, and 28 (29.2%) patients had grade III of LV diastolic dysfunction. There were 77 (80.2%) and 19 (19.8%) patients with good and poor QoL, respectively. This study revealed a significant relationship between the severity of LV diastolic dysfunction and QoL in HFrEF patients with p=0.040. In conclusion, the degree of LV diastolic dysfunction is related to the QoL of HFrEF patients and therefore better comprehensive management strategies should be considered in HFrEF cases to address the impact of LV diastolic dysfunction on QoL.